Relation between Moral Competence and Religiosity: Cognitive and Intuitive Aspects - Trups-Kalne, Ingrīda; Dimdiņš, Ģirts (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the study was to examine whether moral foundations mediate the negative relation between moral competence and orthodox/conservative religiosity. The participants (N = 361, aged 16 to 74) completed the Moral Judgment Test (Lind, 1978, 2008), the 30-Item Full Version of the Moral Foundations Questionnaire (Graham, Haidt & Nosek, 2008), and Huber's (Huber, 2004) Religion’s Centrality Scale. Mediation analysis revealed that the ‘binding’ moral foundations of in-group loyalty, respect for authority, and purity mediate the negative relation between moral competence and orthodox religiosity. These results are in line with Lind’s theoretical prediction that if individuals have more criteria to consider when making moral judgment, it may hamper their performance on moral competence measures, which are typically based on the individual foundations of harm avoidance and justice. The study contributes to understanding differences in social cognition between liberal and conservative religiosity.